Pietismus Handbuch - Breul, Wolfgang; Hahn-Bruckart, Thomas (Mohr Siebeck, 2021)
With almost 80 articles by an array of leading researchers from the fields of theology, historical studies, German studies and other disciplines, the Pietism handbook provides a comprehensive overview of the reform movement of the late seventeenth and eighteenth centuries that continues to shape post-Reformation Protestantism in Western societies to this day.Survey of contentsMit Beiträgen von: Ruth Albrecht, Veronika Albrecht-Birkner, Craig Atwood, Albrecht Beutel, Wolfgang Breul, Mette Birkedal Bruun, Urban Claesson, Zoltan Csepregi, Klaus-Peter Decker, Rudolf Dellsperger, Claudia Drese, Juliane Engelhardt, Katherine Mary Faull, Martin Gierl, Thomas Hahn-Bruckart, Sylvaine Hänsel, Ariel Hessayon, Thomas Illg, Joachim Jacob, Juliane Jacobi, Manfred Jakubowski-Tiessen, Martin H. Jung, Jan van de Kamp, Hans-Georg Kemper, Hans-Martin Kirn, Brigitte Klosterberg, Thomas Kuhn, Fred van Lieburg, Ulf Lückel, Susanne Luther, Benjamin Marschke, Markus Matthias, Kristian Mejrup, Ute Mennecke, Dietrich Meyer, Wolfgang Miersemann, Justus Nipperdey, Lars Cyril Nørgaard, Klaus vom Orde, Hans Otte, Martin Prell, Irmtraut Sahmland, Stefania Salvadori, Wolf-Friedrich Schäufele, Jan Carsten Schnurr, Hans-Jürgen Schrader, Alexander Schunka, Douglas Shantz, Christian Soboth, Malte van Spankeren, Jan Stievermann, Andres Straßberger, Jonathan Strom, Lothar Vogel, Peter Vogt, Andreas Waczkat, Martin Weyer-Menkhoff, Holger Zaunstöck, Peter Zimmerling
Quellen- und Literaturverzeichnis: Seite 639-766
Keywords: Handbook; Aufsatzsammlung; Lehrbuch; Wirkung; Pietismus; Sozialgeschichte; Frömmigkeit; Theologie; Verbreitung; Historische Persönlichkeit; Geschichte